Persepsi Masyarakat Kecamatan Huristak terhadap Kewajiban Berzakat Melalui Baznas Kabupaten Padang Lawas Sumatera Utara - Emrizal Emrizal (IAIN Batusangkar, 2023)
The results of this study are that some of the scholars who participated in the socialization support and agree with the obligation to pay zakat to the BAZNAS institution, but some scholars who do not know and do not participate in the socialization from BAZNAS, think that there is no obligation to pay zakat to the institution and are still required to distribute zakat to the mustahik who are around them. Whereas community leaders have more confidence in the distribution carried out by the amil of the mosque because it can be reflected in the distribution of zakat to their relatives or families, and according to what they have done long ago. Some of them also think that paying zakat to BAZNAS institutions is not mandatory, because there is already an Amil zakat appointed by the community. In addition, they understand that BAZNAS is only a social institution that helps the poor or disaster-affected communities. Then the understanding of muzakki is that they do not know the obligation to pay zakat through BAZNAS, but they have no objection if they have to pay zakat to BAZNAS institutions, provided that these institutions must carry out open and transparent outreach to the public about zakat programs and management and collect zakat